Perinephric Hematoma with Active Arterial Hemorrhage following Extracorporeal Shockwave Lithotripsy - Edward Assaf; Rawad Abou Zahr; Elie Ghabi; Imad Ghantous (Case Reports in Urology)
Subcapsular hematoma is an exceedingly rare complication of extracorporeal shockwave lithotripsy (ESWL) for renal stones with cases demonstrating evidence of active arterial bleeding even more so. A 49-year-old male presented with acute onset right flank pain two hours following ESWL. CT scan with contrast revealed active contrast extravasation consistent with arterial bleeding. The patient was managed with arterial embolization and recovered uneventfully following a 4-day hospitalization.